2022
DOI: 10.1111/andr.13196
|View full text |Cite
|
Sign up to set email alerts
|

Addiction and human male fertility: A systematic review and a critical appraisal

Abstract: Background Addiction is a global problem that has many negative consequences on human health as well as the quality of life. Objectives This review aimed to assess the effect of addiction on human male fertility. Methods A systematic review was conducted on various electronic sites. Results The initial literature search identified a total of 5239 articles in all searched databases. After removing duplicates and application of inclusion/exclusion criteria, 177 were potential articles, 112 were omitted because n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 126 publications
(226 reference statements)
1
7
0
Order By: Relevance
“…Finally, in agreement with Alghobary and Mostafa [ 73 ], it is here felt that future studies should include the use of logistic regression analysis to better understand the effect of specific substances on human male fertility.…”
Section: Discussionsupporting
confidence: 81%
“…Finally, in agreement with Alghobary and Mostafa [ 73 ], it is here felt that future studies should include the use of logistic regression analysis to better understand the effect of specific substances on human male fertility.…”
Section: Discussionsupporting
confidence: 81%
“…He is in the age of 44, which could be already critical for quality of sperm according to Jimbo et al 10 However, taking under consideration all medical exams done, as well as body shape and physical activities (Figure 1), patient had very healthy lifestyle and was in a good condition. In addition to medication, patient worked on addictive habits (smoking, drinking, drugs and medication use, alcohol), 4 sleep pattern, 5 daily sport activities, 19,20 stress level, 3 coffee consumption, 3 food quality, 6 and antioxidants use. 17,18,21,22 Since patient does not smoke or use drugs, only two habits that he changed in this period are reducing alcohol consumption 4-5 drinks per week to 1-2 maximum.…”
Section: Discussionmentioning
confidence: 99%
“…2 The data on marijuana use and male fertility are noted to be heterogeneous, as it has been shown to contribute to poor quality sperm in some studies, with no effect seen in other studies. 5,18,19 Overall, the literature points to a negative impact of marijuana on sperm morphology, while the effect on other semen parameters remains uncertain. 18 The influence of obesity on female fertility is well known, although the impact of obesity on male fertility receives less attention possibly due to less conclusive data.…”
Section: Idiopathic or Unexplained Causesmentioning
confidence: 99%
“…5,18,19 Overall, the literature points to a negative impact of marijuana on sperm morphology, while the effect on other semen parameters remains uncertain. 18 The influence of obesity on female fertility is well known, although the impact of obesity on male fertility receives less attention possibly due to less conclusive data. 20 Certain studies have shown lower counts and less motile sperm and azoospermia in men with obesity.…”
Section: Idiopathic or Unexplained Causesmentioning
confidence: 99%